2022
DOI: 10.3389/fmicb.2022.1018077
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of microbial composition under three tree ecosystems using the stochastic process and network complexity approaches

Abstract: Soil microbes act as “players” in regulating biogeochemical cycles, whereas environmental heterogeneity drives microbial community assembly patterns and is influenced by stochastic and deterministic ecological processes. Currently, the limited understanding of soil microbial community assembly patterns and interactions under temperate forest stand differences pose a challenge in studying the soil microbial involvement during the succession from coniferous to broad-leaved forests. This study investigated the ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
2
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(4 citation statements)
references
References 90 publications
1
2
1
Order By: Relevance
“…This was consistent with the fact that rare subgroup owns a large number of species but a low abundance, which resulted in a more even distribution of abundance than the abundant and medium abundance subgroups 64 , 65 . In addition, the most uniform distribution in broad-leaved forests and the worst distribution uniformity in shrub and coniferous forests, was consistent with the conclusion on the increasing complexity of soil bacterial network from temperate coniferous forests succession to broad-leaved forests in Liupanshan Mountain 66 , which promoted co-existence and niche differentiation by reducing intraspecific and interspecific competition of bacteria 67 . Coordinate points of community structure of each habitat-specialization subgroup of some broad-leaved forests were obviously seperated from that of other stands.…”
Section: Discussionsupporting
confidence: 86%
“…This was consistent with the fact that rare subgroup owns a large number of species but a low abundance, which resulted in a more even distribution of abundance than the abundant and medium abundance subgroups 64 , 65 . In addition, the most uniform distribution in broad-leaved forests and the worst distribution uniformity in shrub and coniferous forests, was consistent with the conclusion on the increasing complexity of soil bacterial network from temperate coniferous forests succession to broad-leaved forests in Liupanshan Mountain 66 , which promoted co-existence and niche differentiation by reducing intraspecific and interspecific competition of bacteria 67 . Coordinate points of community structure of each habitat-specialization subgroup of some broad-leaved forests were obviously seperated from that of other stands.…”
Section: Discussionsupporting
confidence: 86%
“…Another parameter that can impact fungal community assembly processes is plant communities through direct host-microbial interactions and rhizosphere effects ( Martínez-García et al, 2015 ) and indirect mediation of soil physicochemical properties ( Zak et al, 2003 ). The results of this study do not explain the impacts of abiotic factors on fungal community assemblies, but some studies showed that fungal community assemblies could be impacted by seasonal and successional variations ( Liu et al, 2021 ; Kang et al, 2022 ; Wang et al, 2022 ). Our study’s shortcomings accommodate the paucity of evidence of the soil edaphic parameters and the consideration of other environmental variables like diversity vegetation canopies.…”
Section: Discussioncontrasting
confidence: 80%
“…In the calculation of the network, there were eight replicates in each group, and only seven OTUs that were not 0 were selected for correlation calculations out of the eight samples. After obtaining the correlation matrix data, the data were visualized using Cytoscape software (3.7.1) ( Figure 5 ) [ 60 ]. After that, sub-network data such as node, edge, average density, transitivity, diameter, and average path length were calculated for each sample using the “igraph” package [ 61 , 62 ].…”
Section: Methodsmentioning
confidence: 99%